Promoting effect of biogenic AgNPs on Echinops macrochaetus for improving growth parameters and mitigating the toxic effect caused by salinity stress - Salim Khan; Fahad Al-Qurainy; Abdulrahman Al-hashimi; Mohammad Nadeem; Mohamed Tarroum; Abdalrhaman Mohamed Salih; Ossman Hassan Shaikhaldein; Norah Saad Alfarraj (Biotechnology & Biotechnological Equipment)
Nanoparticles may serve as novel plant growth stimulators to improve plant growth as well as protect plants from abiotic stresses. In this study, biogenic silver nanoparticles (AgNPs) were synthesized using the aqueous extract of Fagonia bruguieri and characterized using UV-visible spectroscopy, Zeta potential, transmission electron microscopy (TEM) and Fourier Transform Infrared Spectroscopy (FTIR). The synthesized AgNPs were employed on Echinops macrochaetus as seeds priming, and plants grown in pots were exposed to salinity stress to assess the ameliorating effects based on various parameters. The growth parameters (shoot length) and biomass (shoot, root and leaves weight) decreased in E. macrochaetus exposed to salinity stress alone (40, 80 and 120 mmol/L NaCl) for 90 days. However, seed priming with a low concentration of AgNPs (40 µmol/L) improved the growth of the plant in terms of biomass, shoot length and chlorophyll content alone as well as ameliorated the toxic effect caused by salinity stress. The mitotic index measured by flowcytometry (FCM) indicated genotoxic effects in plants grown at high concentrations of NaCl (80 and 120 mmol/L) as well as plants obtained with 80 µmol/L AgNPs seed priming and exposed to 120 mmol/L NaCl. Thus, an optimum concentration of AgNPs could be used in E. macrochaetus for production of more biomass by modulating the chlorophyll content, proline and antioxidant enzyme activity.